2015
DOI: 10.1515/pjvs-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Natural immunity factors in Polish mixed breed rabbits

Abstract: Mixed-breed rabbits in Poland are widely used for diagnostic and scientific research and as utility animals, therefore there is a need to know their immunological status, as well as their haematological status. In this study natural immunity factors were analyzed in Polish mixed-breed rabbits and Polish mixed-breed rabbits with addition of blood of meet-breed, considering the impact of sex and season of the year (spring, summer, autumn, winter) using measurement of non-specific cellular and humoral immunity pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The absence of gender differences in seasonal variation in neopterin was surprising considering the known gender differences in immune function [67, 68], seasonal changes in immune function [6163], overall seasonality of physiology and behavior [8, 5759], seasonal environmental exposures in the Old Order Amish [6, 47] major occupational differences in the Amish between genders, in particular in the summer [47], and finally, the known effects of gonadal steroids on immune function [67, 71]. The lack of replication suggests that neopterin levels were indeed robust to at least occupation and gender, and possibly to hormonal influences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of gender differences in seasonal variation in neopterin was surprising considering the known gender differences in immune function [67, 68], seasonal changes in immune function [6163], overall seasonality of physiology and behavior [8, 5759], seasonal environmental exposures in the Old Order Amish [6, 47] major occupational differences in the Amish between genders, in particular in the summer [47], and finally, the known effects of gonadal steroids on immune function [67, 71]. The lack of replication suggests that neopterin levels were indeed robust to at least occupation and gender, and possibly to hormonal influences.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, a number of studies have reported sex differences in seasonal variation in immune function with generally higher variation in females in comparison to males, across species [6163]. Males exhibit increased vulnerability to disease and heightened disease severity when compared to females exposed to the same pathogens [6466].…”
Section: Introductionmentioning
confidence: 99%